Evolución y causas de la pobreza en el departamento del Chocó durante el siglo XXI (2018)
In recent years, the department of Chocó has been characterized by social, economic and cultural deterioration, which has led to the deepening of its socio-economic stagnation in the last century; different factors are presented on which several studies have been carried out, trying to give an answer as to why Chocó has the highest rates of poverty in Colombia. In the research carried out, some particular causes are analyzed that today are presented as a great problem in said department, already mentioned among the objectives that are proposed for the study. For corruption in general, and lack of public investment in particular, among other causes. Access roads are very scarce or are not in the best condition, and therefore it is difficult to exit and enter goods and services to and from the department, and its capital Quibdó. In addition, there is a lack of employment opportunities, scarcity of education, health and other causes that negatively affect the well-being of the population.